Transmission and distribution losses of Turkey's power system - (:unkn) unknown (My University, 2010)
In this study, the transmission and distribution losses in Turkey power system were researched. The studies carried out for purpose of determining its illegal use and its socio-economical effects were analyzed. It is impossible to prevent the losses completely in the electric energy system. However, in developed countries, it generally remains below 6%. The lost illegal use rate in Turkey was determined as 14.4%. The cost resulting from only illegal use reaches to values that urge the economy of Turkey with a rate that is 1.7 times of the annual transmission and distribution system investment of the country. To decrease the technical losses, very serious additional energy investment is needed in the country. However, illegal use rate can be decreased to acceptable rates as a result of policy changes and some measures. In the study, some solution suggestions are made to decrease the loss rate that occurs as a result of illegal use.
Keywords: Electrical energy demand; Electricity theft; Energy generation; T&D loses; Turkey